2018
DOI: 10.1080/13697137.2018.1512965
|View full text |Cite
|
Sign up to set email alerts
|

Does anti-Müllerian hormone predict change in menopausal symptoms following risk-reducing salpingo-oophorectomy? A prospective observational study

Abstract: Does anti-Müllerian hormone predict change in menopausal symptoms following risk-reducing salpingo-oophorectomy? A prospective observational study Objectives The aim of this study was to investigate whether serum Anti Müllerian hormone (AMH) predict symptom burden after risk-reducing salpingo-oophorectomy (RRSO) in order to individualize counselling. Methods Patient-reported menopausal symptoms, sexual functioning and psychological distress (depression and anxiety) were assessed one day before (T0), and six we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…We reported a negative correlation between serum AMH concentration and depression severity in our previous study among women with PCOS [ 16 ]. Additionally, similar results of the negative association between AMH and depressive symptoms were also reported in women with salpingo-oophorectomy, and even among young and nulliparous women [ 43 , 44 ]. AMH, expressed by the granulosa cells in ovarian follicles, is usually measured for evaluating ovarian reserve function in patients with secondary amenorrhea [ 45 ].…”
Section: Discussionsupporting
confidence: 73%
“…We reported a negative correlation between serum AMH concentration and depression severity in our previous study among women with PCOS [ 16 ]. Additionally, similar results of the negative association between AMH and depressive symptoms were also reported in women with salpingo-oophorectomy, and even among young and nulliparous women [ 43 , 44 ]. AMH, expressed by the granulosa cells in ovarian follicles, is usually measured for evaluating ovarian reserve function in patients with secondary amenorrhea [ 45 ].…”
Section: Discussionsupporting
confidence: 73%
“…In an attempt to evaluate the link between AMH and the future development of climacteric symptoms, others tried to explore the role of this marker in the population of surgically induced menopause. A small Dutch study evaluated 91 premenopausal women who underwent risk-reducing salpingo-oophorectomy due to their high risk of ovarian cancer [ 47 ]. The authors reported that presurgical AMH levels were not related to the change in psychological distress or endocrine and sexual symptoms following surgery, either at 6 weeks or at 7 months [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small Dutch study evaluated 91 premenopausal women who underwent risk-reducing salpingo-oophorectomy due to their high risk of ovarian cancer [ 47 ]. The authors reported that presurgical AMH levels were not related to the change in psychological distress or endocrine and sexual symptoms following surgery, either at 6 weeks or at 7 months [ 47 ]. A smaller cohort study investigated the development of menopausal symptoms over time in 170 young women who underwent chemotherapy at least 12 months ago and compared the observations with 135 similar-aged controls and 71 controls of late reproductive age [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, there was a negative study results, which was conducted by Jurczak et al [33], that the level of AMH and depressive symptoms was not related in the group of healthy late-reproductive-age women. Vermeulen et al [34] also reported negative results of the association between AMH and change in symptom burden including depression, hot flush, and sexual dysfunctions after salpingo-oophorectomy. On the other hand, a recent study by Golenbock SW et al [35], was reported that there were modest inverse associations between depression and low AMH among young and nulliparous women.…”
Section: Discussionmentioning
confidence: 99%